2017
DOI: 10.1093/pcp/pcx167
|View full text |Cite
|
Sign up to set email alerts
|

Genistein-Specific G6DT Gene for the Inducible Production of Wighteone in Lotus japonicus

Abstract: Prenylated isoflavonoids have been found in several legume plants, and they possess various biological activities that play important roles in both plant defense and human health. However, it is still unknown whether prenylated isoflavonoids are present in the model legume plant Lotus japonicus. In the present study, we found that the prenylated isoflavonoid wighteone was produced in L. japonicus when leaf was supplemented with genistein. Furthermore, a novel prenyltransferase gene, LjG6DT, was identified, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 59 publications
3
16
0
Order By: Relevance
“…A recent work has established that there is a differential regulation of flavonoid and isoflavonoid biosynthetic pathways in L. japonicus in relation to nitrogen metabolism and in response to different stress conditions [ 62 ]. An increase in the level of expression of several genes of the isoflavonoid pathway was observed in response to drought or active photorespiration, which was much more noticeable in a Ljgln2-2 photorespiratory mutant lacking the plastidic isoform of glutamine synthetase (GS2) [ 1 , 62 ] ( Figure 2 ). Therefore, important changes in phenolic metabolism as a result of GS2 deficiency were observed in L. japonicus plants in response to stress.…”
Section: Differential Regulation Of Flavonoid and Isoflavonoid Biomentioning
confidence: 99%
See 3 more Smart Citations
“…A recent work has established that there is a differential regulation of flavonoid and isoflavonoid biosynthetic pathways in L. japonicus in relation to nitrogen metabolism and in response to different stress conditions [ 62 ]. An increase in the level of expression of several genes of the isoflavonoid pathway was observed in response to drought or active photorespiration, which was much more noticeable in a Ljgln2-2 photorespiratory mutant lacking the plastidic isoform of glutamine synthetase (GS2) [ 1 , 62 ] ( Figure 2 ). Therefore, important changes in phenolic metabolism as a result of GS2 deficiency were observed in L. japonicus plants in response to stress.…”
Section: Differential Regulation Of Flavonoid and Isoflavonoid Biomentioning
confidence: 99%
“…Both photorespiration and phenylpropanoid metabolism are mainly related to carbon metabolism, but also to nitrogen metabolism because of the use of amino acids as precursors. Therefore, the use of photorespiratory mutants allowed us to understand the cross-interaction between carbon and nitrogen metabolisms as well as (iso)flavonoid metabolism [ 1 , 94 ]. Previous works have clearly established how a GS2 defect in nitrogen assimilation affects carbon metabolism in this plant [ 1 , 94 , 95 , 96 ].…”
Section: Differential Regulation Of Flavonoid and Isoflavonoid Biomentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, various non-prenylated flavonoids were present in the plant extract, but they were generally much less active than their prenylated counterparts. It has already been reported that prenylation increases the lipophilicity of flavonoids, and hence membrane permeability, enhancing the binding affinity of flavonoids to target biomolecules [35].…”
Section: Wound Healing Activitymentioning
confidence: 98%